2018
DOI: 10.1021/acsinfecdis.7b00230
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Based Peptides for Inhibition of Leukotoxin Activity

Abstract: The Gram-negative bacterium Aggregatibacter actinomycetemcomitans, commonly associated with localized aggressive periodontitis (LAP), secretes an RTX (repeats-in-toxin) protein leukotoxin (LtxA) that targets human white blood cells, an interaction that is driven by its recognition of the lymphocyte function-associated antigen-1 (LFA-1) integrin. In this study, we report on the inhibition of LtxA-LFA-1 binding as an antivirulence strategy to inhibit LtxA-mediated cytotoxicity. Specifically, we designed and synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Follow-up studies ectopically expressed only CD11A/CD18 in non-susceptible cell lines and Lally et al confirmed the lack of endogenous CD11B and CD11C surface expression on K562 cells, so the conclusions could only be related to the interaction of LtxA with LFA-1. In light of the Reinholdt et al results that LtxA is equally cytotoxic to all β 2 integrin species tested and that direct binding only occurs with the β 2 subunit, the previous identification of the β-propeller region of CD11A as required for LtxA activity and recent results from Krueger et al are seemingly contradictory [26,27].…”
Section: Proposed Receptors On Nucleated Cellsmentioning
confidence: 97%
See 3 more Smart Citations
“…Follow-up studies ectopically expressed only CD11A/CD18 in non-susceptible cell lines and Lally et al confirmed the lack of endogenous CD11B and CD11C surface expression on K562 cells, so the conclusions could only be related to the interaction of LtxA with LFA-1. In light of the Reinholdt et al results that LtxA is equally cytotoxic to all β 2 integrin species tested and that direct binding only occurs with the β 2 subunit, the previous identification of the β-propeller region of CD11A as required for LtxA activity and recent results from Krueger et al are seemingly contradictory [26,27].…”
Section: Proposed Receptors On Nucleated Cellsmentioning
confidence: 97%
“…A) LtxA: LFA-1 [24] B) LtxA: CD18 EGF-like domains 2, 3, and 4 within amino acids 500-600 [25] C) LtxA: CD11A β-sheets 1 and 2 of the β-propeller region [26,27] Structural models of LFA-1 and Mac-1, respectively composed of CD11A/CD18 and CD11B/CD18, are shown with labels A through S indicate where potential binding sites for RTX toxins occur, with the published reference for the indicated binding site detailed below.…”
Section: Proposed Receptors On Nucleated Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Making use of the previous work that demonstrated the domains of CD11a targeted by LtxA (Kieba et al, 2007), we synthesized a series of peptides based on the last β‐strand in the first β‐sheet (W1S4) and all four β‐strands in the second β‐sheet (W2S1–W2S4). We found that four of the five peptides inhibited LtxA cytotoxicity in THP‐1 cells (Krueger, Hayes, Chang, Yutuc, & Brown, 2018). This suggests that the peptides bind to LtxA, and inhibit the toxin's interaction with CD11a on the host cells by occupying the binding site on the toxin.…”
Section: Anti‐ltxa Strategiesmentioning
confidence: 99%